2017
DOI: 10.1177/0394632017720055
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production in mammary adenocarcinoma and its microenvironmental cells in patients with or without metastases in regional lymph nodes

Abstract: In recent years, the concept of formation of a sufficiently autonomous cytokine network in a malignant tumour has emerged. In this regard, the data on the role of this network and its signalling pathways in the process of metastasis are an interesting topic. The aim of this study was to evaluate the in vitro cytokine-producing potential of mammary adenocarcinoma (MAC; and cells of its microenvironment) from patients with or without metastases in regional lymph nodes (LNs). By enzyme-linked immunosorbent assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 13 We have also shown that the cytokine-producing potential of IBC-NST biopsy samples derived from primary tumours with metastases to regional lymph nodes is significantly different from that without metastases to lymph nodes. 14 In another study, we showed in a similar model that the cytokine profile of an IBC-NST biopsy sample supernatant with the prevalence of poorly differentiated cells differs from the cytokine profile of an IBC-NST biopsy sample with the prevalence of highly differentiated cells. 15 On the basis of these findings, we have proposed that cultivation of IBC-NST samples in a PA-containing medium may affect differentiation of the IBC-NST cells through stimulated production of certain cytokines, and that the magnitude of this effect may be determined by the initial status of IBC-NST, that is, its differentiation degree and its metastatic potential.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“… 13 We have also shown that the cytokine-producing potential of IBC-NST biopsy samples derived from primary tumours with metastases to regional lymph nodes is significantly different from that without metastases to lymph nodes. 14 In another study, we showed in a similar model that the cytokine profile of an IBC-NST biopsy sample supernatant with the prevalence of poorly differentiated cells differs from the cytokine profile of an IBC-NST biopsy sample with the prevalence of highly differentiated cells. 15 On the basis of these findings, we have proposed that cultivation of IBC-NST samples in a PA-containing medium may affect differentiation of the IBC-NST cells through stimulated production of certain cytokines, and that the magnitude of this effect may be determined by the initial status of IBC-NST, that is, its differentiation degree and its metastatic potential.…”
Section: Introductionmentioning
confidence: 75%
“…Tumour biopsy samples (volume 8 mm 3 ) obtained by trepanobiopsy were placed into two glass vials each containing 1 ml of a medium; one vial contained only the DMEM-F12 medium (for evaluation of spontaneous cytokine production, control experiment), while the second vial contained the above PAs (at the specified concentrations) in the same amount of the medium (for evaluation PA-stimulated cytokine production). [13][14][15] Tumour biopsy samples were cultivated in vitro for 72 h. To obtain the pure supernatant, tumour cells remaining in the vials were precipitated by centrifugation at 900 g for 15 min. Enzyme-linked immunosorbent assays (ELISAs) were performed to determine the concentrations of IL-2, IL-6, IL-8, IL-10, IL-17, IL-18, IL-1β, IL-1Ra, TNF-α, IFN-γ, G-CSF, GM-CSF, VEGF-A and MCP-1 (monocyte chemotactic protein 1) in the supernatant via assay kits from AO Vector-Best.…”
Section: Evaluation Of the Cytokine-producing Potential Of The Tumoursmentioning
confidence: 99%
“…While it was shown that G-CSF is highly expressed in human gastric and colon cancers and promote carcinoma cell proliferation and migration [18], its strong association with IL-10 upon metastasis among gastric cancer patients has not been explored until this work. In other types of cancer, it was shown that indeed such strong association does exist in a pairwise correlations between the cytokine production levels in a culture supernatant of biopsy samples of mammary adenocarcinoma, however; data were lumped together from patients without and with metastases in regional lymph nodes giving a correlation of r(IL-10, G-CSF) = 0.61 and p-value = 0.0012 [34]. We showed a more general role for G-CSF in IL-10 production in our previous study [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Autenshlyus et al found that the concentration of IL-10 was lower in supernatant of cultured mammary adenocarcinoma cells from patients with regional lymph node metastasis as compared with patients without them. These data indicate that IL-10 can play the suppressor role in the cytokine-dependent mechanism underlying metastasis to regional lymph nodes [46].…”
Section: Discussionmentioning
confidence: 74%